THE MEMORIES OF THE CORPORAL GENERAL VSEVOLOD PETRIV AS A SOURCE FOR STUDYING THE MILITARY HISTORY OF THE PERIOD OF THE UKRAINIAN NATIONAL REVOLUTION 1917–1921 - FILINYUK , Anatoliy; YARYCH , Volodymyr (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract: This article is devoted to highlighting the content and informational potential of the memoirs of Corporal General V. Petriv concerning the military history of Ukraine during the Ukrainian Revolution of 1917–1921. It emphasizes that this outstanding Ukrainian figure wrote and published his works and memoirs while in exile. The essence and direction of memoirs’ text as a powerful factual addition to military history through the prism of the author's vision of the place and the important role of the armed forces in the establishment and functioning of the state independence of Ukraine are noted. The analysis was carried out on the basis of understanding the history and lessons of the liberation struggles of the Ukrainian people at the turn of the first and second decades of the 20th century.